Warm Climate Production Guidelines for Echinacea - Rick Schoellhorn; Alexis A. Richardson (EDIS)
This is one of the great moments in time when a renowned but limited perennial flower has the roof blown off of its genetic potential. The advances in Echinacea breeding we will be seeing emerge on the market in the next few years are some of the most exciting changes I've seen a long time. I'm hoping this is the beginning of not only some fantastic new hybrids but also increased awareness of some of the lesser known species. This document is ENH 993, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date November 11, 2004.